The challenges of supporting nursing students in clinical education - Seyedeh Roghayeh Jafarian-Amiri; Ali Zabihi; Mojtaba Qanbari Qalehsari (Wolters Kluwer Medknow Publications, 2020)
Clinical education requires creating a supportive atmosphere for learners and nursing students, who need support to be prepared for their future profession. The purpose of this study is to investigate the challenges of supporting the nursing students in clinical education. This article reviewed studies conducted between 2009 and 2019 with the keywords including support, challenge, students, education, and nursing using SID, Magiran, IranMedex, Google Scholar, Elsevier, and PubMed as databases. Among the 926 articles obtained during the two review stages, which were based on the inclusion and exclusion criteria and the first one analyzed the title and the abstract and the second one analyzed the whole article, ultimately 32 articles were selected for the study. The types of articles used in this study are as follows: qualitative (16 articles), descriptive analytical and cross-sectional (12 articles), review (3 articles), and mixed-methods (1 article). The focus of all studies was on the students' clinical education environment. The participants of the studies were undergraduate nursing students (in 22 articles), graduate students (in 2 articles), nursing instructors and students (in 4 articles), and nursing instructors and managers (in 1 article). Most of the challenges of supporting the students included violence, fear, and anxiety; socio-cultural challenges, environmental-organizational stresses; and ineffective clinical education. The findings of this study showed that nursing students face many challenges in the clinical setting. Therefore, the managers of educational and health-care centers should give a high priority to their students' support programs.